ANALISIS PENGGUNAAN TWIN BLOCK PADA PERAWATAN MALOKLUSI DENTOSKELETAL KELAS II DIVISI 1 DISERTAI RETROGNATI MANDIBULA BERDASARKAN CERVICAL VERTEBRAL MATURATION STAGE - Deta Putri Futuhat, Arlette Suzie P, Meirina Gartika (ODONTO : Dental Journal, 2018)
Background:Class II division 1 dentoskeletal malocclusion with mandibularretrognatic can be treated with twin block appliance. The objectives of this studyare to analyse twin block appliance based on mandibular dimension and anteriorfacial height changes, and to determined the most effective time base on CVMSto begin the treatment.Method: The type of research was a retrospective analysis study usingsecondary data. The sample was 14 lateral cephalometric radiographs beforeand after treatment with twin block appliance. It was taken in IKGA RSGM FKGUNPAD 2010 to 2016. Statistic analysis used paired t-test.Results: Study shows that there is a significant change (p<0.05) in mandibulardimension and anterior facial height after treatment with twin block appliance.Changes in mandibular dimension including total mandibular length, mandibularbody length, ramus height, and gonial angle. Changes in anterior facial heightincluding lower anterior facial height and total anterior facial height. The CVMSIII group showed statistically significant result with the biggest improvement.Conclusion: The use of twin block appliance in Class II division 1 dentoskeletalmalocclusion with mandibular retrognatic could change mandibular dimensionand anterior facial height. Apart from that, CVMS III was found to be the mosteffective time to start the treatment with twin block appliance